2021
DOI: 10.1111/nin.12403
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of intergenerational co‐parenting during the postpartum period in modern China: A qualitative exploratory study

Abstract: Most studies conducted in the West on the role played by intergenerational families in co-parenting have focused mostly on families with a single mother or those in difficult circumstances, while little is known about the experiences of members of intergenerational intact families during the early postpartum period. This study aimed to explore the intergenerational co-parenting experiences of young parents and grandmothers in China, focusing on how they shared the responsibility of caring for the new mother an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 46 publications
(107 reference statements)
1
22
0
Order By: Relevance
“…Moreover, fathers are less likely than mothers to engage in coparenting coalitions. Even in dual‐worker families, fathers tend to regard their role as the “breadwinner” rather than caregiver (Conn et al, 2013; Xiao & Loke, 2021) and may be excluded from coparenting if mothers doubt their childcare competence (Wang & Schoppe‐Sullivan, 2021). Moreover, the gendered division of labor is subject to family contexts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, fathers are less likely than mothers to engage in coparenting coalitions. Even in dual‐worker families, fathers tend to regard their role as the “breadwinner” rather than caregiver (Conn et al, 2013; Xiao & Loke, 2021) and may be excluded from coparenting if mothers doubt their childcare competence (Wang & Schoppe‐Sullivan, 2021). Moreover, the gendered division of labor is subject to family contexts.…”
Section: Resultsmentioning
confidence: 99%
“…Despite daily childrearing problems, coparenting alliances develop capacity to cope with predictable family transitions and irregular critical events in the long run (Walsh, 2012). Normative transitions, such as a newborn's arrival or grandparental involvement in an immigrant family, prompt the whole family to reconsider its role distribution, thus forcing individuals to adapt to the changing environment and reconfigure their roles to shoulder childcare responsibilities (Chiu & Ho, 2020; Dolbin‐MacNab et al, 2021; Xiao & Loke, 2021; Xie & Xia, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of division of labor assumed that the satisfaction with the partner's contributions regarding arrangements of childrearing issues might represent the overall coparenting relationship. However, as a recent qualitative study showed, many Chinese mothers were more satisfied with the emotional support that they received from their husbands in childrearing without demanding that they provide help in infant care (Xiao & Loke, 2021). In this sense, the parent's involvement in actual parenting labor and the partner's satisfaction with it might not violate the overall coparenting relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of family harmony, couple conflict (Im & Ispa, 2022), feelings of unattachment toward one's spouse (Cowan et al, 2019), and decreased sensitivity toward parents and children (Ferrar et al, 2020) have been noted. Postpartum intergenerational conflict is a relatively new term in which family tension increases from negative triangular interactions between the infant's parents and grandparents who engage in childrearing from childbirth to 1 year (Xiao & Loke, 2021). Yet, the iStock/kate_sept2004 culture teaches women and girls to obey their parents and to yield to the wishes of family elders, which is a precursor for developing post partum depression (Do et al, 2018;Ta Park et al, 2017;Zou et al, 2020).…”
mentioning
confidence: 99%